Potential of Mutual Funds in Facing Changes in the Macroeconomic Situation - Tubagus, Rahmat Nurseha; Gunarsih, Tri; Safitri, Julia (Indonesian Journal of Business Analytics, 2024)
In pandemic conditions, Indonesia's macroeconomic situation experienced very sharp changes. Inflation and BI 7 Day Repo Rate (BI7DRR) set record lows. Gross Domestic Product (GDP) has also experienced a decline, which last occurred during the economic crisis in 1998. This research was conducted to analyze the influence of inflation, BI7DRR and GDP on the Net Asset Value (NAV) of conventional and sharia mutual funds as well as the influence of mutual fund types on mutual fund NAV. Panel data regression was carried out on mutual fund NAV, inflation, BI7DRR and GDP data collected quarterly during the 2013-2022 period. Dummy variables are used in regression analysis to determine whether there is a significant difference between the NAV of islamic and conventional mutual funds. The estimation results using the random effect model show that inflation and BI7DRR are not proven to have a significant effect on the NAV of sharia and conventional mutual funds, while GDP is proven to have a positive and significant effect on the NAV of sharia and conventional mutual funds. It is also not proven that there is a significant difference in the NAV of sharia and conventional mutual funds, so it is stated that the type of mutual fund has no effect on the NAV of mutual funds.